2016
DOI: 10.1111/pai.12505
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of multiple asthma loci identified by genomewide association studies on asthma and spirometric indices

Abstract: IL13 and GSDMB are replicated as asthma genes. Rs2305480 of GSDMB is also associated with low FEV1 , FVC, and FEV1 /FVC among asthmatics. Moreover, SLC22A5, IL13, SMAD3, and GSDMB interact to modulate spirometric indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…However, their importance in modulating lung function remains poorly studied. This study showed that GSDMB _rs2305480 was associated with patients’ FEV 1 /FVC at any single year as well as longitudinal changes in this spirometric index, the former of which was consistent with what we found in our previous cross‐sectional study . In a recent GWAS, McGeachie et al evaluate the genetic underpinnings of lung function growth in 581 CAMP participants with asthma.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, their importance in modulating lung function remains poorly studied. This study showed that GSDMB _rs2305480 was associated with patients’ FEV 1 /FVC at any single year as well as longitudinal changes in this spirometric index, the former of which was consistent with what we found in our previous cross‐sectional study . In a recent GWAS, McGeachie et al evaluate the genetic underpinnings of lung function growth in 581 CAMP participants with asthma.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies reported genes on 17q21 locus, such as ORMDL3 and GSDMB , to be the most widely replicated asthma genes in different ethnic groups . The recent GWAS also reported GSDMB to be associated with severe asthma exacerbations in Swedish preschool children .…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that the manifestations of allergic disorders are the results of complex interactions between genetic and environmental factors. Using both the candidate gene and the genomewide association approaches, many studies of genetics susceptibilities for allergic disorders in Chinese have been performed . As exemplified by studies of asthma genetic studies, there are substantial differences in the frequencies of single nucleotide polymorphisms (SNPs) and haplotype blocks for asthma genes in Chinese and other populations .…”
Section: International Collaboration and Research In Chinamentioning
confidence: 99%
“…Using both the candidate gene and the genomewide association approaches, many studies of genetics susceptibilities for allergic disorders in Chinese have been performed. [28][29][30][31][32] As exemplified by studies of asthma genetic studies, there are substantial differences in the frequencies of single nucleotide polymorphisms (SNPs) and haplotype blocks for asthma genes in Chinese and other populations. 33 As demonstrated by the complexity of the interaction between polymorphisms of the CD14 gene and exposures to microbes on the risk of asthma, 34 future international collaborative efforts with simultaneous assessment of relevant environmental exposures are needed to clearly understand the contribution of various susceptibility genes in the pathogenesis of allergic disorders in different ethnic groups.…”
Section: International Collaboration and Research In Chinamentioning
confidence: 99%
“…The overexpression of GSDMC in metastatic melanoma cells is an exception to its apoptotic role (9). In addition to cancer, genome-wide association studies (GWAS) have revealed a correlation between single nucleotide polymorphisms (SNPs) in both the protein coding and transcriptional regulatory regions of the neighboring genes GSDMA, GSDMB, and ORDML3 in the 17q12.2.1 loci and susceptibility to diseases such as asthma (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), type 1 diabetes (21,22), Crohn's disease, ulcerative colitis (22,23), and rheumatoid arteritis (22,24). The mechanisms by which these SNPs affect susceptibility to developing complex-trait inflammatory diseases are unknown.…”
mentioning
confidence: 99%